Alteration of Basal Ganglia and Right Frontoparietal Network in Early Drug-Naïve Parkinson’s Disease during Heat Pain Stimuli and Resting State - Tan, Ying; Tan, Juan; Deng, Jiayan; Cui, Wenjuan; He, Hui; Yang, Fei; Deng, Hongjie; Xiao, Ruhui; Huang, Zhengkuan; Zhang, Xingxing; Tan, Rui; Shen, Xiaotao; et al. (Frontiers in Human Neuroscience, 2015)
Background: The symptoms and pathogenesis of Parkinson’s disease (PD) are complicated and accurate diagnosis is difficult, particularly in early-stage. Functional magnetic resonance imaging is noninvasive and characterized by the integration of different brain areas at functional connectivity (FC). Considering pain process in PD, we hypothesized that pain is one of the earliest symptoms and investigated whether FC of the pain network was disrupted in PD without pain. Methods: Fourteen early drug-naïve PD without pain and 17 age- and sex-matched healthy controls (HC) participated in our test. We investigate abnormalities in FC and in functional network connectivity in PD compared with HC during the task (51 °C heat pain stimuli) and at rest. Results: Compared with HC, PD showed decreased FC in basal ganglia network (BGN), salience network (SN) and sensorimotor network in two states respectively. FNC between the BGN and the SN are reduced during both states in PD compared with HC. In addition, the FNC associated with right frontoparietal network (RFPN) was also significantly disturbed during the task. Conclusion: These findings suggest that BGN plays a role in the pathological mechanisms of pain underlying PD, and RFPN likely contributes greatly to harmonization between intrinsic brain activity and external stimuli.